Health Related Quality of Life, Social Support and Social Capital of Mothers of Children with Cancer - Nicolaou, Christiana; Kouta, Christiana; Papathanassoglou, Elizabeth; Middleton, Nicos (My University, 2016)
Background.The diagnosis of childhood cancer is particularly stressful with adverse health effects for all the family. Social support and the wider social context can act as buffer, perhaps as long as the support provided is appropriate (stressor-specific hypothesis).Methods.A descriptive comparative study of health-related quality of life (HRQoL) using the SF-36 survey in a sample of 52 mothers of children with cancer (MCC, 93% response) from the only pediatric oncology referral centre on the island compared to 208 mothers of age/gender matched healthy children in the absence of population norms (MHC, 89% response). In each group, the magnitude of the association of HRQoL with perceived social support (MOS–SSS) and social capital (SCQ) was assessed and compared.Results.Significant reduced scores on the SF-36 Mental Health Component and all four domains (effect sizes −0.4 to −0.7 SD, p < 0.01) was observed among MCC. Even though there were no differences in perceived social support between the groups, the protective effect on mental health was restricted to mothers of healthy children (1.62 95% CI = 1.02, 2.23 per 10 unit increase in social support score) but no association was observed in mothers of children with cancer (0.08 95% CI=-1.16, 1.32); p for effect modification=0.03. A similar picture emerged in terms of social capital. In contrast, social support and social capital showed strong positive associations with Physical Health in both study groups, and somewhat stronger among MCC.Conclusions.Whilst HRQoL is positively associated with social support and social capital in a sample of mothers from the general population, among mothers of children with cancer the potential protective effect appears restricted to physical and not mental health, which is particularly poor, giving support to the stressor-specific hypothesis of social support and hence the importance and need to design and evaluate psychosocial programs targeted to the individual circumstances and needs of these families.
Keywords: Diagnosis; Childhood cancer; Health-related quality of life; Mothers of children with cancer (MCC)